EFFECTIVE STRATEGIES FOR TEACHING ESL VOCABULARY (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: The following article provides information about effective ways of teaching vocabulary in ESL classes. It also defines the term vocabulary and reveals the role of vocabulary in improving reading comprehension of students.